Strategic Facilities Management (FM) for heritage buildings in Malaysia/ Nurul Fadzila Zahari ... [et al.] - Zahari, Nurul Fadzila; Abd Ghani, Aida Affina; Khalid, Mohd Khazli Aswad; Kamarudin, Hikmah; Abdul Rashid, Robiah (Universiti Teknologi MARA, Perak, 2024)
It is becoming increasingly common to apply adaptive reuse to preserve and make use of older structures. Multiple stakeholder scenarios are frequently involved in adaptive re-use; consequently, coordination or administrative concerns may limit the design of adaptable facilities for the purpose of preserving cultural heritage and maximising operational efficiency. This research explores the applicability and benefits of an FM-led adaptive reuse technique to overcome the coordination challenge, a concept not previously explored in the existing literature. Methods of observation and literature review are utilised in this paper. Using field observations, publicly available policies, and project data, this study was able to discover the attitudes and requirements of stakeholders about facilities management (FM) in adaptive reuse projects, including heritage buildings. The paper elaborates on the way FM coordinates adaptive reuse for the benefit of stakeholders and society. Adaptation of heritage buildings, user experience, and community effects are all factors that FM accounts for. The facilitation of innovative facility design, effective decision-making, and public engagement are all made possible by it. Urban regeneration demonstrates the heritage advantage of FM. The research has not addressed the significance of FMled business strategy for adaptive reuse in heritage buildings, nor has it discussed the benefits those strategies offer. Not only does it develop a heritage conservation management evaluation methodology, but it also reveals the strategic functions that FM plays.